Soil sealing on example of the Jedrzychow residential area in Zielona Gora, Poland - Kostecki, Jakub; Greinert, Andrzej; Drab, Michał; Mik, Łukasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The progressing urbanization leads to the growth of buildings within the cities and taking up new areas for investments. Uncontrolled urban sprawl entails a number of consequences resulting in the soil sealing of the areas which has been permeable so far. Cutting off deeper soil layers from gas exchange and access to water causes a reduction in biological activity and biodiversity. That is why EU considers soil sealing as one of the main problems of the 21st century. The paper attempts to analyze the progressing urbanization on the one of the Zielona Góra housing estates - Jędrzychów Residential Area.
Keywords: urban soils; urbanization; residential; soil sealing; soil degradation; gleba miejska; urbanizacja; osiedle mieszkaniowe; uszczelnianie; degradacja gleby